Suárez de Salazar "cita" a Cornelio Galo: un postrer episodio del Pseudo-Galo en el Renacimiento - Navarro López, Joaquín Luis (Euphrosyne: Revista de filología clássica, 1995)
The 17th-Century scholar from Cadiz J.B.Suárez de Salazar included in his work entitled Grandezas y antigüedades de la isla y ciudad de Cádiz a Latin epitaph concerning a woman called Lycoris. Suárez de Salazar determinedly thinks she was the most celebrated mistress of the ill-fated poet Cornelius Gallus and, according to Renaissance Gallan literary standards, he quotes Maximian’s second elegy as Gallus’s. Our labour has consisted in the accomplishment of the introduction and edition with a commentary of Suárez de Salazar's peculiar text.